Burden and trends of stroke attributable to dietary risk factors from 1990 to 2019 in the Belt and Road Initiative countries: an analysis from the global burden of disease study 2019 - Zhang, Yue; Luo, Zheng; Yi, Juan; Zhu, Junjie; Qiu, Yun; Xu, Xiaoyun; Xie, Wanying; Wu, Jinyi; Lv, Huihui; Mou, Changhua; Zhang, Wei; Li, Xiaopan (Frontiers in Nutrition, 2023)
Objectives: This study aimed to compare the burden and trends of stroke attributed to dietary risk factors in the Belt and Road (“B&R”) countries from 1990 to 2019. Methods: The 2019 Global Burden of Disease (GBD) Study was used to gather information on the burden of stroke attributable to dietary risk factors. Numbers and age-standardized rates (ASRs) of deaths, disability-adjusted life years (DALYs) were determined in 1990 and 2019 among the “B&R” countries. The average annual percent change (AAPC) was used to analyze the temporal trends of diet-induced stroke DALYs from 1990 to 2019 and in the final decade (2010-2019) by Joinpoint regression analysis. Results: In 2019, the absolute number of stroke deaths and DALYs attributable to dietary risk factors were 671,872 cases (95% UI 436,354-937,093) and 1.67 million cases (95% UI 1.15-2.24) in China. We found geographical differences in mortality and DALYs of diet-attributable stroke among member countries, with Bulgaria, Hungary and Serbia being the three highest countries in 1990, Bulgaria, North Macedonia and Montenegro in Central Asia in 2019. The ASRs of diet-induced stroke mortality and DALYs were generally declining in most member states from 1990 to 2019, however, the corresponding metrics in Mongolia remained high. The fastest decline in ASR of mortality and DALYs for diet-induced stroke was seen in Estonia, Eastern Europe, with AAPC values of -7.09% (95%CI: -7.72%, -6.46%) and -6.62% (95%CI: -7.20%, -6.03%), respectively. We noted a substantial downward trend in ASR of mortality and DALYs from diet-induced stroke changes in the final decade (2010-2019) for most member states. The ASR of DALYs for diet-induced stroke decreased greater in females than in males. For those aged 50-74, the DALYs for stroke due to dietary risk factors in all other member countries of the “B&R” showed a decreasing trend, except for the Philippines, which rose (AAPC=2.13, 95%CI: 1.40%-2.87%) and Turkmenistan, which remained stable (AAPC=0.05, 95%CI: -0.43%-0.33%). Conclusion: The burden of diet-induced stroke varies substantially across “B&R” countries and threaten public health, relevant evidence-based policies and interventions should be adopted to address the future burden of stroke in “B&R” countries through extensive collaboration.